2017
DOI: 10.1167/iovs.17-22097
|View full text |Cite
|
Sign up to set email alerts
|

The 3D Retinal Capillary Circulation in Pigs Reveals a Predominant Serial Organization

Abstract: PURPOSE. To establish a model of the retinal capillary circulation in pigs, which in many aspects is close to the human retina.METHODS. Using high density confocal microscopy image stacks of immunolabeled porcine retinal whole mounts, microvessels close to the optic nerve head were traced in three dimensions. The direction of flow of individual capillaries was deduced from their arteriolar and/or venous connections.RESULTS. From major arteries, second-order arteries traversed the nerve fiber layer and resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 39 publications
9
37
0
Order By: Relevance
“…Toussaint et al 1 reported that RPCs came from the disc and differed from other retinal capillaries, whereas Henkind et al 2,17 suggested that these capillaries originated from retinal arterioles. Moreover, in a recent study by Fouquet et al, 18 With circumpapillary OCT B-scans, Muraoka et al 19 demonstrated the existence of major retinal vessels in the RNFL. However, HR-OCTA in the present study revealed the presence of major vessels in the central macular area in a slab for the GCL; importantly, this slab showed the capillary-free zone around arteries and arterioles, facilitating differentiation of arterial and venous systems as well as capillary beds and retinal microcirculatory units consisting of arterial and venous channels with intervening capillaries.…”
Section: Discussionmentioning
confidence: 96%
“…Toussaint et al 1 reported that RPCs came from the disc and differed from other retinal capillaries, whereas Henkind et al 2,17 suggested that these capillaries originated from retinal arterioles. Moreover, in a recent study by Fouquet et al, 18 With circumpapillary OCT B-scans, Muraoka et al 19 demonstrated the existence of major retinal vessels in the RNFL. However, HR-OCTA in the present study revealed the presence of major vessels in the central macular area in a slab for the GCL; importantly, this slab showed the capillary-free zone around arteries and arterioles, facilitating differentiation of arterial and venous systems as well as capillary beds and retinal microcirculatory units consisting of arterial and venous channels with intervening capillaries.…”
Section: Discussionmentioning
confidence: 96%
“… 8 , 16 , 31 , 43 There is excellent evidence for the anatomical arrangement of capillaries in peculiar spider-like “vortices” in the DCP, in the current, as well as other OCTA 14 , 15 and histologic studies. 4 , 5 , 44 However, the presence of the central venular connection of these vortices should not be conflated with a primary venous function of the DCP, given the requirement for high oxygen in the OPL. Physiologically, it seems the high demand and consumption of oxygen in the OPL precludes the possibility that this capillary layer (DCP) would consist exclusively of a venular drainage basin, carrying deoxygenated blood.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the seminal work by Paul Henkind 39 in 1967 who found that the RPC are not derived from arterioles within the optic disk but rather from arterioles that supply the peripapillary regions. Toussaint and colleagues 17 speculated that the RPC might be supplied by the SCP, but it was the recent work using pig eyes, by Fouquet et al 40 that showed that the SCP is the exclusive recipient of blood flow from retinal arterioles. Our study was able to confirm similar findings in human eyes.…”
Section: Discussionmentioning
confidence: 99%